Implementation of the trilingual policy through the Advanced Teacher Training System for secondary schools teachers of «Computer science», «Physics», «Chemistry» and «Biology» in English - Nurzhumbayeva, A.Z.; Sarzhanova, G.B. (KSU Publ., 2019)
The article is devoted to the process of implementing the trilingual policy, on the example of organizing advanced training courses by three additional educational centers, such as: Nazarbayev University Educational Excellence Centre, «USTAZ» Professional Learning Centre, JSC «ORLEU» Institute for professional development. Considerable attention is paid to how the above-mentioned organizations conducted training of secondary school teachers to the teaching Biology, Chemistry, Physics, and Computer science in English. The main methods and approaches used by these organizations are described and analyzed, such as an integrated approach to learning to improve language skills and development of skills, a cascade learning model and a new philosophy of education and the use of modern innovative educational technologies to ensure the improvement of the quality of education in Kazakhstan. In conclusion, the authors show the necessity to research the transformation of advanced teacher training system, based on the fact that it is an integral part and a tool for implementing the policy of all educational reforms.
«Информатика», «Физика», «Химия» жəне «Биология» пəндері бойынша ағылшын тілінде жалпы білім беретін мектептердің педагог кадрларының біліктілігін арттыру курстарында Біліктілікті арттыру үштілділік бағдарламасын жүзеге асыру
Реализация Программы трехъязычия на курсах повышения квалификации педагогических кадров общеобразовательных школ по предметам «Информатика», «Физика», «Химия» и «Биология» на английском языке
Keywords: teacher training courses; trilingual policy; Cascade Model of Training; implementation of the reform